Dispositions and tissue residue of zearalenone and its metabolites α-zearalenol and β-zearalenol in broilers - Buranatragool, Kawinnart (Toxicol Rep, 2015)
Zearalenone (ZEA) is a secondary fungal metabolite produced mainly by a Fusarium graminearum. To clarify the toxicokinetics, and residues of ZEA and its major metabolites α-zearalenol (α-ZOL) and β-zearalenol (β-ZOL) in chickens, ZEA was then administered intravenously (iv) or orally (po) to broiler chickens at a dosage of 1.2 mg/kg body weight. The concentrations of ZEA, α-ZOL and β-ZOL in the plasma and various tissues were quantified using LC–MS/MS. The plasma concentrations of ZEA were measurable up to 2 h after iv and po administration, and the concentrations of α-ZOL and β-ZOL were detected up to 4 h after both types of administration. A two-compartment model was developed to describe the toxicokinetic of ZEA in broilers. The values of t(1/2β) and V(d) were 1.36 ± 0.29 h and 6.40 ± 0.89 l/kg, respectively. The absolute oral bioavailability was 29.66 ± 5.6%. ZEA, α-ZOL and β-ZOL were measurable in the vital organs after po administration. These results suggest that ZEA is absorbed from the gastrointestinal tract and it has ability to penetrate into the various tissues of broiler chickens.